Adolescents’ Emotion Regulation Strategies Questionnaire: Initial Validation and Prospective Associations With Nonsuicidal Self-Injury and Other Mental Health Problems in Adolescence and Young Adulthood in a Swedish Youth Cohort - Zhou, Ya; Daukantaitė, Daiva; Lundh, Lars-Gunnar; Wångby-Lundh, Margity; Ryde, Adam (Frontiers in Psychiatry, 2020)
Although there is extensive research indicating the vital role of functional emotion regulation (ER) in healthy psychological development, such research has neglected examination of adolescents. One potential reason for this neglect is the lack of valid ER instruments developed specifically for adolescents. Further, the available ER instruments for adolescents usually require elaborate forms of cognitive reasoning about the internal sequences of cognitions and emotions. To address these limitations, we developed the Adolescents’ Emotion Regulation Strategies Questionnaire (AERSQ), a self-report instrument of adolescents’ commonly used ER strategies in daily life, and examined its psychometric characteristics in a 10-year, three-wave cohort of Swedish youths (original N = 991, mean age = 13.7, 14.8, and 25.3 at waves 1, 2, and 3, respectively). Exploratory (wave 1 data) and confirmatory (wave 2 data) factor analyses revealed a five-factor structure for the AERSQ: rumination/negative thinking, positive reorientation, communication, distraction, and cultural activities. We observed gender differences for most ER strategies in adolescence. We also evaluated the associations between the AERSQ subscales and mental health (self-harm; psychological difficulties including hyperactivity, conduct problems, emotional problems, and peer problems; prosocial behavior; depression; anxiety; stress; flourishing; and life satisfaction) across the three time points. Rumination/negative thinking had the strongest relationships with these mental health indicators, both cross-sectionally and longitudinally, in both genders. Distraction and cultural activities were less related to mental health, especially prospectively. Although the AERSQ showed good test-retest reliability and predictive validity over a 10-year period, the low internal consistency of two of its subscales (distraction and cultural activities) indicate that it may benefit from further development both in terms of the included items and psychometric testing.